Simultaneous cardiocerebral infarctions: a five-year retrospective case series reviewing natural history - Cheryl Zhiya Chong; Benjamin Yong-Qiang Tan; Ching-Hui Sia; Thet Khaing; Leonard Leong Litt Yeo (Singapore Medical Journal)
Introduction: Concurrent cardiocerebral infarction (CCI), a rare condition defined as simultaneous occlusions in the cerebrovascular and coronary vessels, has high mortality but very limited literature on optimum treatment methods. A better understanding of the natural history and effect of treatment would improve patient outcomes. Methods: Using our prospective stroke database from 2014 to 2018, ten consecutive patients with CCI were identified (incidence = 0.29%). We recorded patient demographics, cardiovascular risk factors, cardiac and cerebral occlusions, circumstances of admission and management of each patient. Patient notes and imaging findings were reviewed to determine the underlying cause of CCI. Results: Median National Institute of Health Stroke Scale score was 15 (range 4–27). Mean patient age was 59 years and 90% were men. Two patients were treated with intravenous tissue plasminogen activator (IV tPA) only and three underwent endovascular treatment in both the cerebral and coronary vessels sequentially. One patient underwent percutaneous coronary intervention (PCI) only and two underwent PCI after IV tPA therapy. Two patients were conservatively treated due to poor premorbid status. At the three-month follow-up, five patients had excellent functional outcomes (modified Rankin Scale 0–1) while three died. Conclusion: CCI is a rare but devastating clinical scenario, with high incidence of morbidity and mortality. Treatment strategy can impact patient outcome, and further research is warranted on the ideal acute and post-reperfusion treatments for CCI. In this series, IV tPA at stroke doses appeared to be the preferred initial step for its treatment, with subsequent coronary or cerebral endovascular therapy, if necessary.